Effect of Bamboo Species Subject to Location for Long Fiber Associated with Textile Properties - Abdullah, Mohamad Syafiq; Mohd Nazrul Roslan (Progress in Engineering Application and Technology, 2022)
Bamboo has been one of the most numerous plants remained in a natural population in recent decades. However, bamboo is rapidly growing rapidly due to its use in textile applications as well as its status as the world's most sustainable plant. Textile fiber has to be physically long, light, and have an uniform thickness. Bamboo fibers contain a large amount of cellulose and lignin. Bamboo has an extremely short physical length, less than 4 mm in single fiber form. This natural property may have an impact on the mechanical properties of fiber bundles or long fiber production in textile manufacturing. Furthermore, different species of bamboo make it extremely difficult to harvest long and fine bamboo fibers. As a result, the tensile behaviour of bamboo fibers over a wide range of species and regions must be thoroughly studied. The purpose of this research is to determine the tensile properties of bamboo fiber bundles from five commercially available bamboo species in Malaysia. The top, middle, and basal (bottom) locations of bamboo fiber bundles were mechanically extracted and tested. The tenacity and fineness of long bamboo fibers were investigated. Among those species, basal of buluh duri had the highest fineness among all species with approximately 31.72 tex, while middle of buluh semeliang had the highest tenacity with 126.88 cN/tex.